¿Como establecer y manejar un banco comunitario de semillas? Manual del productor agricola. Aspectos tecnicos: Cuaderno 2 de 3 - Vernooy, Ronnie; Bessette, Guy; Sthapit, B.R.; Gupta, A. (Bioversity International, 2018)
This handbook is a companion to Community seed banks: concept and practice: facilitator handbook by Ronnie Vernooy, Bhuwon Sthapit, and Guy Bessette (Bioversity International 2017). The three booklets making up this handbook were written and designed for rural producers who are interested in establishing, supporting, and managing a community seed bank. Each booklet focuses on a theme presented by the members of a community seed bank in Africa, Asia, and Latin America. The booklets are be available also in English and French. Translation and adaptation to the local language is encouraged.